Kajian Pemanfaatan Layanan Rujukan Perpustakaan Universitas Indonesia Tahun 2019 - Kalarensi Naibaho (Media Pustakawan, 2020)
Reference service is one of the leading services in the college library. In the digital era, the concept of reference services is transformed along with technological developments. The reference service transformation also took place at the University of Indonesia Library. Reference collections are dominated by e-resources, therefore the service concept has also changed. The purpose of this study is to determine the level of user satisfaction with the reference service, and the development of what needs to be done by the librarian in improving the UI Library reference service. The data collected by using a questionnaire survey, which was circulated online and directly. Research respondents were 361 UI postgraduate students. Data were processed using SPSS version 17. Validity and reliability tests were performed using Pearson Product Moment. The reliability test is done by Cronbach’s Alpha.  The results of the study are mapped into 4 SWOT components, Strength: complete e-resources collection, adequate access facilities, competent librarians. Weakness: lack of facility maintenance, some facilities are lacking, access via remote is often problematic. Opportunity: some services are not yet known to users, service socialization and promotion must be more intense. Threat: maintenance of facilities is not under the coordination of the library so that it is difficult when needing quick repairs, reference librarians are decreasing due to retirement, and the lack of HR development programs. It is recommended that the UI Library conduct more intensive coordination with DSTI and DPPF related to technical issues that are often complained by respondents.